Letter - Glastonbury Trades and labour council, 9 May 1926 (Glastonbury)
1926-05-09 "Letter - Glastonbury Trades and labour council, 9 May 1926" [g0335001.jpg], 9 May 1926, Glastonbury Trades and Labour Council Local Organisation